P doped molybdenum dioxide on Mo foil with high electrocatalytic activity for the hydrogen evolution reaction. Issue 5 (13th January 2016) - Xie, Xiao; Yu, Ruijin; Xue, Na; Yousaf, Ammar Bin; Du, Hong; Liang, Kuang; Jiang, Nan; Xu, An-Wu
Abstract : P doped MoO2 nanoparticle films on Mo foil used as electrodes for an efficient and stable electrocatalytic hydrogen evolution reaction (HER). Abstract : As a clean and renewable energy carrier, hydrogen generation has attracted much interest and the electrocatalytic hydrogen evolution reaction (HER) is one of the most promising ways of low-cost hydrogen production in the future. In this work, we report the fabrication of noble-metal-free P doped MoO2 nanoparticles (NPs) on Mo foil as electrodes for highly efficient HER. Benefiting from a strong interaction between P doped MoO2 NPs and Mo foil as a current collector, the obtained electrode exhibits excellent HER activity with a small onset overpotential of 80 mV, a large cathodic current density of 10 mA cm −2 at 135 mV and a small Tafel slope of 62 mV per decade, much better than MoO2 -based catalysts. Additionally, a P doped MoO2 film/Mo foil electrode displays good stability even after 2000 potential cycles in acidic media. The development of a novel route to prepare P doped MoO2 on Mo foil as an active HER catalyst broadens the insight of designing noble- metal-free HER efficient catalysts with cost-effective and environmentally friendly advantages.